Kajian Perolehan Sertifikasi Profesi Internasional Bagi Lulusan Jurusan Sistem Informasi - Hudiarto, Hudiarto (Bina Nusantara University, 2011)
Having a professional certificate in information systems and information technology fields means having the recognition for related skills and knowledge requested by the industry. Some countries and institutions have tried to bridge these needs by organizing conferences and seminars. Information systems department of Bina Nusantara University always tries to meet those needs. One effort is to introduce the Enterprise Architecture method initiated by Bernard for use in the course of information systems and information technology strategic planning. The results of this activity suggest that obtaining international certification requires the implementation of learning in a referenced standard. This approach is expected to accelerate the acquisition of professional certification for graduates majoring in information systems and technology.